1998
DOI: 10.1287/opre.46.1.46
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Pricing of Priority Services

Abstract: We consider the problem of a service facility that offers m different priority classes to its n customers, and sets a tariff (price-schedule) to maximize profit. Each customer must use the service facility and will select an output rate and the priority classes used to maximize profit. The problem is formulated as a noncooperative game. We show that equilibrium output rates and assignments to priority classes can be determined by solving the integrated system problem (ISP) that maximizes the joint profit of al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 24 publications
0
32
0
Order By: Relevance
“…See Nonlinear Pricing by Robert Wilson (1993) that offers an invaluable set of methodologies and insights to tariff design in the electric power industry. In the queueing context, see Rao and Peterson (1998) who demonstrate that a special form of nonlinear tariff (i.e., two-part tariff) exists to induce optimal output rates and priority assignment for a service facility.…”
Section: Introductionmentioning
confidence: 99%
“…See Nonlinear Pricing by Robert Wilson (1993) that offers an invaluable set of methodologies and insights to tariff design in the electric power industry. In the queueing context, see Rao and Peterson (1998) who demonstrate that a special form of nonlinear tariff (i.e., two-part tariff) exists to induce optimal output rates and priority assignment for a service facility.…”
Section: Introductionmentioning
confidence: 99%
“…Well-cited research on priority pricing in priority queues can be found in Dolan (1978), Mendelson and Whang (1990) and Rao and Petersen (1998). In these articles, the authors propose a priority pricing mechanism based on self-revelation theory so that each arriving customer is dispatched with the proper priority, and the target of the proposed priority pricing mechanism is to maximize either social welfare (Dolan, 1978;Mendelson and Whang, 1990) or the firm's profit (Rao and Petersen, 1998). In the research on priority pricing in priority queues, the firm does not guarantee the delivery dates, and customers make decisions only based on the expected leadtime.…”
Section: Background Literaturementioning
confidence: 99%
“…Queueing systems in which customers can purchase priorities have been studied in [14,10,13,2,7,12]. The bribing model for priority in queues, introduced in [12] is as follows.…”
Section: Introductionmentioning
confidence: 99%
“…Such systems are considered in [2,14,4]. Systems with multiple FIFO queues, each with its own server were considered in, among others, [9,6] and such a system with an admission price for each queue was analyzed in [8].…”
Section: Introductionmentioning
confidence: 99%